Bengal's Administrative Re-Organisation A Survey of the Rowlands Committee Report - Basu,D.N.; Biswas,C.C. (Fwd) (Calcutta Book Company, 1945)
The Rowlands Committee was constituted to report principally on the suitability of the Governmental structure at present existing in Bengal and to suggest remedies for improving the machinery of Government, so that the activities of Government in the Post-War period may be directed to the fullutilisation of the material and human resources of the Province. When all the world over, not by any means excluding India and her great provinces, there had been so much talk and writing about Post-War Reconstruction, it was only apposite that Bengal with her manifold peculiar problems crying for solution, should find it imperatively necessary to overhaul her present administrative machinery; and Bengal is grateful to her Governor Mr R. G Casey for having set up a competent and authoritative Committee for framing a well-thought out and comprehensive scheme for the purpose. It is, indeed, a mattet for congratulation that in the midst of the pressing preoccupations of the concluding stages of the Second World War, a Committee with such a personnel and presided over by a person of the eminence of Sir Archibald Rowlands, could be constituted and their report obtained within such a short space of time.